2023
DOI: 10.3389/feduc.2022.1057651
|View full text |Cite
|
Sign up to set email alerts
|

Student experience scale: Factor analysis in higher education institutions

Abstract: IntroductionIn the context of higher education, the student experience (SX) has an important impact on student satisfaction and the perceived value of the training service received. For these reasons, higher education institutions (HEIs), which are focused on student-centred learning, need to know more about the experience that results from student interaction with the service and support systems that meet their needs in these institutions. However, despite the progress made in the analysis of SX, further rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…This step led us to a more in-depth analysis of regrouping the items within certain dimensions of skills. Indeed, we conducted factor analysis (Amado Mateus et al, 2023) to obtain consistent dimensions that were confirmed with Cronbach's alpha.…”
Section: Data Analysismentioning
confidence: 95%
“…This step led us to a more in-depth analysis of regrouping the items within certain dimensions of skills. Indeed, we conducted factor analysis (Amado Mateus et al, 2023) to obtain consistent dimensions that were confirmed with Cronbach's alpha.…”
Section: Data Analysismentioning
confidence: 95%
“…Управління студентським досвідом являє собою студентоцентричний підхід, спрямований на поліпшення академічних, соціальних, адміністративних і позанавчальних аспектів студентського життя. Ефективне управління таким досвідом вимагає постійної уваги до потреб та очікувань студентів, а також розроблення стратегій і практик, які підтримують студентів упродовж усього їхнього шляху в університеті (Amado et al, 2023). Ключові елементи управління студентським досвідом можуть включати в себе:…”
Section: 1unclassified